2019
DOI: 10.5194/amt-12-5303-2019
|View full text |Cite
|
Sign up to set email alerts
|

Measurement techniques for identifying and quantifying hydroxymethanesulfonate (HMS) in an aqueous matrix and particulate matter using aerosol mass spectrometry and ion chromatography

Abstract: Abstract. Oxidation of sulfur dioxide (SO2) in the gas phase and in cloud and fog water leads to the formation of sulfate that contributes to ambient particulate matter (PM). For severe haze events with low-light conditions, current models underestimate the levels of sulfate formation that occur exclusively via the oxidation of sulfur dioxide. We show here that measurement techniques commonly used in the field to analyze PM composition can fail to efficiently separate sulfur-containing species, resulting in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(93 citation statements)
references
References 44 publications
1
92
0
Order By: Relevance
“…S2d). In addition, Moch et al and Dovrou et al found that the AS22 column could not fully separate HMS and sulfate, while AS12A was able to successfully separate HMS and sulfate (Moch et al, 2018;Dovrou et al, 2019). Actually, HMS dissociates into SO3 2− and HCHO rapidly in the eluent due to the short characteristic time for HMS dissociation at pH 12, and HMS concentration is measured in the form of sulfite in ion chromatography ( Fig.…”
Section: Offline Sample Collection and Ion Chromatography Analysismentioning
confidence: 99%
“…S2d). In addition, Moch et al and Dovrou et al found that the AS22 column could not fully separate HMS and sulfate, while AS12A was able to successfully separate HMS and sulfate (Moch et al, 2018;Dovrou et al, 2019). Actually, HMS dissociates into SO3 2− and HCHO rapidly in the eluent due to the short characteristic time for HMS dissociation at pH 12, and HMS concentration is measured in the form of sulfite in ion chromatography ( Fig.…”
Section: Offline Sample Collection and Ion Chromatography Analysismentioning
confidence: 99%
“…In terrestrial ecosystems, direct effects of acid deposition to foliage include leaching of cations, altered stomatal function, and changes in wax structure (Cape, 1993). Acid deposition can exacerbate soil acidification (Binkley and Richter, 1987), resulting in loss of soil base cations, leaching of nitrate, and mobilization of aluminum, affecting terrestrial ecosystem health and the quality of water delivered to streams and lakes (Driscoll et al, 2007). Apart from reactive nitrogen, atmospheric deposition is also a significant source of limiting and trace nutrients such as phosphorus (P), iron (Fe), and copper (Cu), especially in the remote oceans (Mahowald et al, 2008;Myriokefalitakis et al, 2018).…”
Section: The Importance Of Atmospheric Aciditymentioning
confidence: 99%
“…S2d). In addition, Moch et al (2018) and Dovrou et al (2019) found that the AS22 column could not fully separate HMS and sulfate, while AS12A was able to successfully separate HMS and sulfate. HMS dissociates into SO 2− 3 and HCHO rapidly in the eluent due to the short characteristic time for HMS dissociation at pH 12, and the HMS concentration is measured in the form of sulfite in ion chromatography ( Fig.…”
Section: Offline Sample Collection and Ion Chromatography Analysismentioning
confidence: 99%